2017
DOI: 10.1111/jgs.15004
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Clinical Presentations of Acute Phase Chikungunya Virus Infection in Older Adults

Abstract: Only 8.2% of the older adults presenting in the acute phase of CHIKV have typical forms, suggesting that the most-frequent clinical presentation of CHIKV in older adults differs from that in younger individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
52
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(55 citation statements)
references
References 29 publications
3
52
0
Order By: Relevance
“…In the current study population, underdiagnosis was more frequent than overdiagnosis in older adults and that underdiagnosis was significantly more frequent in older (21.6%) than in younger (2.8%) adults (p<.001). This is consistent with the more frequent atypical presentation in older adults and the fact that fever and arthralgia are often absent (in > 40% of older adults) . CVI does not require any specific treatment, and management mainly consists of painkillers and antipyretics.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…In the current study population, underdiagnosis was more frequent than overdiagnosis in older adults and that underdiagnosis was significantly more frequent in older (21.6%) than in younger (2.8%) adults (p<.001). This is consistent with the more frequent atypical presentation in older adults and the fact that fever and arthralgia are often absent (in > 40% of older adults) . CVI does not require any specific treatment, and management mainly consists of painkillers and antipyretics.…”
Section: Discussionsupporting
confidence: 78%
“…Other authors have previously studied the rate of diagnostic errors in the ED in individuals with pulmonary tuberculosis and identified atypical presentation and unresponsiveness as factors associated with greater rate of misdiagnosis. It was previously reported that there is a higher rate of atypical presentations of CVI in individuals aged 65 and older . In the current study population, underdiagnosis was more frequent than overdiagnosis in older adults and that underdiagnosis was significantly more frequent in older (21.6%) than in younger (2.8%) adults (p<.001).…”
Section: Discussionsupporting
confidence: 41%
See 2 more Smart Citations
“…We previously showed that elderly patients who develop unclassifiable CVI have more comorbidities than those with typical or atypical presentation. The comorbidities alone do not explain the frailty of elderly subjects , but they do account for a large part of it.…”
Section: Discussionmentioning
confidence: 99%